Peningkatan Pengetahuan Masyarakat Tentang Manfaat Fe Pada Kegiatan Kalteng Expo Tahun 2023 - Fitriani Ningsih; Lensi Natalia Tambunan; Cindi Patikasari; Dea Cristin; Vina Astika; Mayang Puspitasari (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2023)
People, especially women of childbearing age, are prone to anaemia because they lose a lot of blood during menstruation. Women of childbearing age who suffer from anaemia have a high risk of anaemia during pregnancy. This will have an impact on the inhibition of fetal growth and development and potentially lead to complications of pregnancy and childbirth. Therefore, women of childbearing age (WUS) need to take Blood Addition Tablets (TTD) once a week. To overcome these problems, it is necessary to increase knowledge about the benefits of fe tablet consumption. The results of this activity were attended by 39 women of childbearing age who visited Kalteng Expo 2023. During the activity, the residents were very enthusiastic. This can be seen in the liveliness of the residents following the counselling activities and the increase in knowledge from before and after being given education.